Contributions of physical therapy in the dehospitalization process of children with chronic diseases: literature summary - Silva, Luany Sousa Gama; Nunes, Silvânia Azevedo da Silva; Araujo, Yara Beatriz Martins; Santos, Amanda Cabral dos (Revista Coleta Científica, 2023)
The research aims to carry out qualitative bibliographical research in order to understand the role of the physiotherapist in the process of dehospitalization of children with chronic diseases. since physiotherapy is able to promote health, child development and the prevention of injuries and support the family so that it is prepared to deal with a new reality. Along with a multidisciplinary team, the physiotherapist must act by assessing the emotional, social and economic conditions of the child and the family member or guardian, assessing the home's physical structure, guiding the family regarding activities, postures, habits, in addition to providing care for the child. according to the kinetic-functional diagnosis.